Etnopedagogi Batang Garing Suku Dayak Ngaju sebagai Nilai Pendidikan Karakter Peduli Lingkungan - Wurdianto, Kukuh; Norsandi, Dedy; Fitriana, Evi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research aims to analyze the Batang Garing symbol of the Dayak Ngaju tribe in Central Kalimantan based on an ethnopedagogical perspective, especially in environmental care character education. The research design used is an ethnographic research design that focuses on the Batang Garing symbol. This ethnographic research consists of 6 stages, selecting an ethnographic project; asking ethnographic questions; collecting ethnographic data; taking notes; analyzing the data, and writing the results of the ethnographic research. The results of this study explain that Ethno pedagogy raises the values of local wisdom as an important part of the educational process and the civilizing process. Dayak Ngaju tribe adheres to a conservationist understanding which is taken from the philosophy of the Batang Garing symbol which contributes to treating the natural environment. the value of character education in each part of the Batang Garing symbol, among others: the